PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE PEER LESSON PADA MATERI SEGIEMPAT DI KELAS VII SMP NEGERI 21 PONTIANAK - Hendra Rukmana; Ahmad Yani T; Romal Ijuddin (Universitas Tanjungpura, 2019)
AbstractThis study aimed to determine and describe the effectiveness of students learning with the implementation of the strategy of active learning tipe peer lesson on the material quadrilateral in class VII SMP N 21 Pontianak. The method that used is Experimental research design with Posstest. The sample of this research wan students of class VII D. Instruments used in the form of the essay and the observation sheet. Based on the results of the analysis obtained information that the effectiveness of students learning with the implementation of the strategy of active learning tipe peer lesson is with the category of effective. Furthermore, the average percentage of student learning activities that use learning strategies active type Perr Lesson is 75,92% by category active. The average percentage of adherence to the syntax of student learning using learning strategies active type Perr Lesson is 4,13% with very good category or keterlaksaan syntax learning effective. The average percentage of student learning outcomes using learning strategies active type Perr Lesson is 87.5% with category very good. The average percentage of response student learning using learning strategies active type Perr Lesson is 70.94% with category good. Keywords: Strategy of Active Learning, Peer Lesson, Quadrilateral.